The application of the principles of the convention on women in awig-awig pakraman village - Ni Nyoman Sukerti (Indonesia Prime, 2017)
This research aims to study the task of the village in Bali related pakraman by the ratification of the women's Convention into law Number 7 in 1984 about the passage of the Convention on the Elimination of all forms of discrimination against women. The community's customary law in Pakraman Village Bali is called based on the applicable local Bali province number: 3 years Pakraman Village of 2003. One of the tasks of the village Pakraman is making the rule of law (awig-awig). The enactment of related laws, the legal issues that arise: what are the principles of the Convention established the woman had already formulated in the awig – awig village pakraman? The legal issues observe by using the normative legal method by relying on legal materials and material non-law. Also, problems also assessed by the theory of legal pluralism of Sally Falk Moore, i.e., Semi-autonomous social field theory.Based on search results and study materials of the law, in this case, some awig-awig Pakraman village, results or findings indicate that women's Convention established the principles namely equality and justice between men and women has not yet been applied awig-awig in the pakraman village. So, based on the theory of legal pluralism is examined from Sally Falk Moore, where local laws (awig-awig) turned out to be stronger regarding State law are dealt face. The things which can know from the provisions of article (pawos) from some awig-awig who examined it turns out women's Convention principles, namely equality and justice between men and women has not yet applied in the awig – awig pakraman village. That means that the discriminative customary law was still so strong so the benchmark in the Association life pakraman. So, in conclusion, the principles of the Convention on women has not been applied in the awig – awig pakraman village, so that still reflect discriminatory against women.This research needs to be continued with empirical legal research to find out why the principles of the Convention on women has not applied to the awig – awig pakraman village